2017
DOI: 10.1186/s12943-017-0671-2
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulated expression of long noncoding RNAs in gynecologic cancers

Abstract: Cancers of the female reproductive system include ovarian, uterine, vaginal, cervical and vulvar cancers, which are termed gynecologic cancer. The emergence of long noncoding RNAs (lncRNAs), which are believed to play a crucial role in several different biological processes, has made the regulation of gene expression more complex. Although the function of lncRNAs is still rather elusive, their broad involvement in the initiation and progression of various cancers is clear. They are also involved in the pathoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
109
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(110 citation statements)
references
References 145 publications
(136 reference statements)
1
109
0
Order By: Relevance
“…The identity and characteristics of lncRNAs dysregulated in EEC, including MALAT1, HOTAIR, SRA, H19, OVAAL, RP11395G12.3, LA16313D11.11, CASC2, ASLNC04080, and ENST0000050294 were reviewed (Takenaka et al 2016). The roles and functions of selected lncRNAs, i.e., MALAT1, HOTAIR, H19, MEG2, CCA2, ANRIL, OCAL, BC2200, and CUDR in cancers of the female reproductive system including endometrial, ovarian, and cervical cancers were recently reviewed (Hosseini, et al 2017). H19 is a well-studied imprinted, maternallyexpressed lncRNA that encodes miR-675 and is overexpressed in breast, HCC, prostate, colorectal, esophageal, bladder, and many other cancers, but is downregulated in adrenocortical neoplasms (reviewed in (Huarte 2015)).…”
Section: Lncrnas In Ecmentioning
confidence: 99%
“…The identity and characteristics of lncRNAs dysregulated in EEC, including MALAT1, HOTAIR, SRA, H19, OVAAL, RP11395G12.3, LA16313D11.11, CASC2, ASLNC04080, and ENST0000050294 were reviewed (Takenaka et al 2016). The roles and functions of selected lncRNAs, i.e., MALAT1, HOTAIR, H19, MEG2, CCA2, ANRIL, OCAL, BC2200, and CUDR in cancers of the female reproductive system including endometrial, ovarian, and cervical cancers were recently reviewed (Hosseini, et al 2017). H19 is a well-studied imprinted, maternallyexpressed lncRNA that encodes miR-675 and is overexpressed in breast, HCC, prostate, colorectal, esophageal, bladder, and many other cancers, but is downregulated in adrenocortical neoplasms (reviewed in (Huarte 2015)).…”
Section: Lncrnas In Ecmentioning
confidence: 99%
“…lncRNAs are different from mRNAs, which are a group of ribonucleic acids more than 200 nucleotides and challenge the classical central dogma of molecular biology. They involve in processes including proliferation, invasion, migration, and others features of tumors through epigenetic, transcriptional, and post‐transcriptional routes such as modifying histones, interfering with the transcription of the target protein and binding to the protein into a nucleic acid protein complex, despite they cannot be translated to proteins …”
Section: Introductionmentioning
confidence: 99%
“…They involve in processes including proliferation, invasion, migration, and others features of tumors through epigenetic, wileyonlinelibrary.com/journal/mc transcriptional, and post-transcriptional routes such as modifying histones, interfering with the transcription of the target protein and binding to the protein into a nucleic acid protein complex, despite they cannot be translated to proteins. 4,5 In the existing studies, lncRNA DLEU1 as a new research focus, is closely related to the tumor. Most studies have revealed that there is deletion of DLEU1 gene that maps to a region at chromosoma 13q14.3 in some solid tumors and hematopoietic malignancies, such as atypical or classical spindle cell lipomas, chronic lymphocytic leukemia, and small lymphocytic lymphoma.…”
mentioning
confidence: 99%
“…lncRNAs are crucial regulators in various biological processes such as cell proliferation, differentiation, metastasis, and death. Quite a few lncRNAs have been reported to be aberrantly expressed in cervical cancer cells, and they were supposed to play important roles in the progression of cervical cancer and be potential diagnostic biomarkers (9)(10)(11)(12)(13)(14).…”
mentioning
confidence: 99%